2018
DOI: 10.1186/s12995-017-0184-3
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement of formic acid, methanol and ethanol in vitreous and blood samples of postmortem by headspace GC-FID

Abstract: BackgroundFormic acid (formate) is the main reason for toxicity and death through methanol poisoning. The simultaneous determination of methanol, ethanol, and formate in the body can help to discover the cause of death and is useful in the diagnosis of acute methanol poisoning. The measurement of formate is not yet available in Iran. With regard to the increasing rate of methanol poisoning and its related mortality in Iran, as well as the main role of formate in methanol poisoning, this study was designed to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…A bivariate logistic regression model was performed separately for the independent variables to evaluate degrees of association with risky driving behavior (dependent variable). The independent variables with a < 0.2 p value [41] in this type of analysis were exported to a multivariable analysis to examine the effects of potential confounders. We selected the forward variable selection method in the multivariable logistic regression model since it was assumed to be relatively more conservative types.…”
Section: Methodsmentioning
confidence: 99%
“…A bivariate logistic regression model was performed separately for the independent variables to evaluate degrees of association with risky driving behavior (dependent variable). The independent variables with a < 0.2 p value [41] in this type of analysis were exported to a multivariable analysis to examine the effects of potential confounders. We selected the forward variable selection method in the multivariable logistic regression model since it was assumed to be relatively more conservative types.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, FID gives a better overall quantitative representation in complex biological samples where traditional MS analysis often is challenged by ion interference effects (36). Further, in a comparison of the non-esterified or free fatty acids quantitative results between the TLC/GC-FID and the GC-MS platforms demonstrated that the GC-MS concentrations of palmitic acid, vaccinic acid, oleic acid, linoleic acid, dihomo-γ-linolenic acid and docosapenta-(4,7,10,13,16)-enoic acid are generally higher than those measured by TLC/GC-FID (11) indicating higher sensitivity and detector-bias as far as MS is concerned.…”
Section: Resultsmentioning
confidence: 99%
“…Combined TLC/GC-FID analysis when compared to GC-MS as the two methods for analysis of human serum lipids, allowed identification and quantification of only eight metabolites in common (arachidonic acid, eicosanoic acid, linoleic acid, oleic acid, palmitelaidic acid, palmitic acid, stearic acid and tetradecanoic acid) (11), suggesting significant complementarity of FID and MS analysis of the human metabolome. Previously, ethanol, methanol, and formate concentrations were measured by headspace GC-FID analysis in vitreous and blood samples collected postmortem (16).…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol, in particular ethanol, is one of the most significantly consumed drugs worldwide. As far as we know, alcohol significantly contributes to the total number of hospital admissions and deaths, mainly including those due to car accidents and overdose [1,2]. The molecule which is responsible for alcohol intoxication is the ethanol (C 2 H 6 O).…”
Section: Introductionmentioning
confidence: 99%
“…Present in all alcoholic beverages, ethanol reaches the blood vessel system through normal digestion. Recognized as a toxin, ethanol is destroyed by the body; mainly in the liver, as it filters blood [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%